Correlation of Status of Mastoid with Outcomes of Myringoplasty with Cortical Mastoidectomy in Mucosal Otitis Media with High Risk Perforation - Shrestha, Asmita; Bhattarai, Hari; Rayamajhi, Pabina; Pradhananga, Rabindra B (Journal of Institute of Medicine Nepal, 2021)
Introduction Chronic mucosal otitis media is one of the common disease prevalent in our society. This study was done to correlate the status of mastoid with outcomes of myringoplasty with cortical mastoidectomy in mucosal otitis media with high risk perforation. Methods This prospective, observational study was done at Department of Otorhinolaryngology and Head and Neck Surgery, Tribhuvan University Teaching Hospital. Thirty-four patients of ag|e 15 and above with chronic mucosal otitis media having high-risk perforation undergoing cortical mastoidectomy with myringoplasty were included. The status of middle ear, aditus, and mastoid air cells were assessed. Post-operatively, patients were assessed for graft uptake and hearing after three months. The post-operative graft uptake and hearing results were correlated with the peroperative status. Four patients who had preoperative sensorineural hearing loss were studied in terms of graft uptake only. Results The graft success rate in patients with normal mastoid air cells was 90% whereas in diseased cases was 71.4% which was statistically not significant with p value 0.20. The success rate in terms of hearing was 68.8% in normal mastoid whereas it was 64.3% in diseased mastoid which was statistically not significant with p-value of 1. Conclusion In correlation with the status of mastoid air cells with graft uptake and hearing result, the observed differences were not statistically significant. However, averages of post-operative air conduction threshold and air-bone gap of all cases were better as compared to preoperative levels.